Amc equity research / the future of the big screen - Farinha, Manuel Salgueiro Do Santos Roque (2022)
Our paper is an equity research report on AMC Entertainment Holdings, the world's largest movie theater company, based primarily in the United States. The major value drivers we considered for our valuation were attendance, average ticket price, and attendance per theatre, which served as a foundation for developing company estimates before using the chosen valuation model, the Adjusted Present Value. Our final recommendation was taken into consideration, with certain risk factors to our valuation, resulting in a stock price of $2.26, as well as a sensitivity study and a scenario analysis to enhance the work done in the company's analysis.